Pengaruh Opini Audit, Reputasi KAP, dan Financial Distress terhadap Auditor Switching - Abdi, Aisha Nabila; Handayani, Dian Fitria (Universitas Negeri Padang, 2025)
This study aims to examine the impact of audit opinion, the reputation of the KAP (Public Accounting Firm), and financial difficulties on auditor turnover. The data used in this study consists of annual financial reports from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. The purposive sampling method was applied to select the data. Logistic regression analysis was employed to analyze the data. The study's findings indicate that audit opinion is associated with auditor turnover, while the reputation of the KAP is negatively related to auditor turnover. Additionally, financial difficulties are found to be related to auditor turnover. Future studies could consider including other variables, such as audit fees and audit delays, as well as other factors that might influence auditor turnover.